The re-existence of indigenous peoples: The path from Inculturation to Interculturality in the thought of Raúl Fornet-Betancourt - MENEZES, Magali (Utopía y Praxis Latinoamericana, 2022)
The present text will seek to critically analyze the paths and implications of the theoretical/practical exercise of inculturation in the Abya Yala cosmologies. Rául Fornet-Betancourt approaches the concept of inculturation as a dominant paradigm, which finds in comparative philosophy an important tool for its maintenance. He criticizes what imposes itself as the orgin of all and any thought that claims to be philosophical. The Western tradition, which produces a concept of logos, denies the plurality of thoughts and the possibility of giving new meaning to the very understanding of philosophy. It is necessary to take the path of interculturality in order to relearn how to think from the indigenous peoples’ perspective.